Operating Room Management in the Pandemic Era - Wisni, Anggrieni (Budapest International Research and Critics University, 2021)
The pandemic in Indonesia has been declared a non-natural national disaster since March 13. 2020(MOH, 2020). As health workers working in the operating room, they must prioritize safety principles to be able to provide the best service in the era of the COVID-19 pandemic. During the COVID-19 pandemic, the standard of hospital room facilities must be a concern so that there is no transmission from patients. The operating room needs to be designed to have the right placement, as well as the right room and equipment design, in order to create a service flow that protects hospital staff and families/communities who come for patients. Appropriate facility standards must be prepared by hospital management so that patient care can be carried out properly. This article aims to discuss good forensic and operating room service standards, and explore options for providing operating rooms for type C and D hospitals or mobile hospitals.